The association of serum clusterin levels and Clusterin rs11136000 polymorphisms with Alzheimer disease in a Turkish cohort - Gamze Guven; Ebru Ozer; Basar Bilgic; Hasmet Hanagasi; Hakan Gurvit; Ebba Lohmann; Nihan Erginel-Unaltuna (Neurological Sciences and Neurophysiology, 2020)
Objectives: Several large-scale genome association studies have shown that variants in the “Clusterin”' (CLU) gene are important risk factors for Alzheimer's disease (AD). It has also been shown that plasma CLU levels were elevated in patients with AD and associated with disease severity and progression. In this study, we aimed to investigate whether the CLU rs11136000 polymorphism was associated with AD in our cohort of Turkish patients. We also evaluated the association of serum CLU levels and rs11136000 genotypes between patients and controls. Materials and Methods: Genotyping was performed in 327 patients who were diagnosed as having AD (mean age: 67.2 ± 10.8 years) and 344 controls (mean age: 57.7 ± 13.1 years). The rs11136000 genotypes were determined using quantitative real-time polymerase chain reaction with hydrolysis probes. Serum CLU levels were assessed in 25 patients with AD and 10 controls using enzyme-linked immunosorbent assay. Results: Our results showed no significant difference in genotype and allele frequencies of CLU rs11136000 polymorphisms between patients with AD and controls. Serum CLU levels in patients with AD did not differ from those of the controls. Furthermore, serum CLU levels showed no major difference between carriers of CC and TT + CT genotypes in the controls and patients with AD. Conclusion: Our results suggest that the CLU rs11136000 polymorphism is not associated with AD in our Turkish patients, and rs11136000 genotypes may not have an effect on serum CLU levels.